MEMBANGUN KEPERCAYAAN DIRI ANAK USIA DINI MELALUI KEGIATAN BERKELOMPOK: KAJIAN TEORETIS DALAM PERSPEKTIF SOSIAL-EMOSIONAL - Billa Putri Bunga (LPPM IAD Probolinggo, 2026)
Self-confidence is a fundamental aspect of social-emotional development in early childhood, influencing children’s ability to interact, make decisions, and face challenges within the learning environment. This study aims to theoretically examine how group activities can serve as an effective strategy for fostering self-confidence in early childhood through positive social experiences, collaboration, and emotional support from peers and educators. This research employs a literature study method by reviewing scientific articles, academic books, and research findings from at least the last five years. The analysis was conducted using content analysis techniques to identify the relationship between group activities and self-confidence development based on social-emotional theories, Erikson’s initiative stage, Vygotsky’s social interaction theory, and the concept of self-efficacy. The findings indicate that structured, collaborative, and developmentally appropriate group activities effectively enhance children’s sense of competence, courage, and independence. Therefore, group activities can be utilized as a strong pedagogical approach to support the development of self-confidence in early childhood.Keywords: Self-confidence; early childhood; group activities.